Spectral features of Gd2O3 modified Sm3+ doped lithium strontium borate glasses for solid-state laser applications. (1st May 2023) - Ullah, I.; Sarumaha, C.S.; Angnanon, A.; Khan, I.; Shoaib, M.; Khattak, S.A.; Kothan, S.; Sangwaranatee, N.; Rooh, G.; Kaewkhao, J.
Abstract: We report the synthesis of Sm-doped Gd2 O3 -modified borate glasses that radiate orange light. Structure modification features, energy transfer (ET), concentration-dependent emission, integral scintillation efficiency, and laser performance are all thoroughly investigated. These glasses are appropriate for near UV excitation lasers because they exhibit strong near ultraviolet (UV) absorption. Using the Judd-Ofelt (JO) theory and the absorption and emission spectra, we determine the oscillator strength, stimulated emission cross-section, radiation transition probability, and branch ratios as spectral characteristics. We examine the lifetime and photoluminescence (PL) spectra of Sm 3+, which is UV-sensitized. The ET between Gd and Sm and from Sm to luminescence centers is what causes the PL from UV to visible/orange, which is achieved at varied excitation wavelengths between 275 and 403 nm. The ET between the Gd 3+ and Sm emission centers is confirmed; as the Gd 3+ level varies from 0 to 10 mol%, the ET efficiency from Gd 3+ to Sm emission centers improves by 6 times. We also determine how ET affects quantum efficiency, donor emission decay kinetics, and donor-acceptor luminescence. We also note the color correlation temperature (CCT) [1629 K], color purity value (99%), and Commission of Illumination coordinates (CIE) as (0.595, 0.403), under 400 excitations. These characteristics demonstrate that these glasses can be used to create orange-laser devices that are excited by near-ultraviolet light.